A method for preparing a core-shell structure phase hydrorefining catalyst

Through the preparation method of the core-shell structure-phase hydrogenation catalyst, the problems of the pore volume and specific surface area of ​​the existing bulk hydrogenation catalyst are solved, and the efficient hydrodesulfurization and nitrogen removal performance of the catalyst is achieved, which is suitable for treating inferior distillation fractions Oil.

CN116943678BActive Publication Date: 2025-02-11CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202210393448.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-15
Publication Date
2025-02-11
Estimated Expiration
2042-04-15

AI Technical Summary

Technical Problem

The pore volume and specific surface area of ​​the existing bulk hydrogenation catalysts are small, which makes it difficult for reactant molecules to approach the catalyst surface, the utilization rate of active metals is low, and there are problems of "ammonia nitrogen" and NOX contamination during the preparation process, which increases costs.

Method used

Using the preparation method of a core-shell structure-phase hydrogenation catalyst, a first slurry containing Ni, Si, Mo and a second slurry containing Ni, W are generated through the first and second gel forming reactions, and then aged, dried and Roasted, and finally desalted in the organic acid solution to form a core-shell structure phase catalyst with a larger pore volume and pore size.

Benefits of technology

The prepared catalyst has a large pore volume and specific surface area, a uniform dispersion of active centers and high utilization rate. It is suitable for the hydrodesulfurization and nitrogen removal processes of distillate oils, especially to effectively treat inferior distillate oils and reduce the occurrence of side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116943678B_ABST
    Figure CN116943678B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a core-shell structure phase hydrorefining catalyst, comprising the following contents: (1) gelling, aging and filtering a first precipitant, a sodium molybdate solution and a solution containing Ni and Si to obtain a filter cake of a first slurry, and then treating it with a mixed aqueous solution of aluminum salt and organic alcohol to obtain a mixed slurry; (2) adding a Ni-containing solution, a sodium tungstate solution, a second precipitant and the mixed slurry obtained in step (1) to a reactor containing water and an oily liquid to gel and age them to generate a second slurry; (3) filtering, drying and molding the slurry to obtain a molded product; (4) soaking the molded product in an organic acid solution, and desalting the soaked molded product to obtain a catalyst. The preparation process of the method is clean and pollution-free, and the prepared catalyst has a core-shell structure, a large pore volume and a large pore size, and is used in processes such as distillate hydrodesulfurization and denitrogenation, and has high hydrodesulfurization and hydrodenitrogenation reaction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalyst preparation, and in particular relates to a method for preparing a core-shell structure phase hydrorefining catalyst. The hydrorefining catalyst is used in processes such as distillate oil hydrodesulfurization and denitrogenation. Background Art

[0002] In order to improve the competitiveness of catalysts in the market and meet the increasingly stringent environmental regulations, it is urgent to use relatively low-priced raw materials to prepare catalysts and use nitrogen-free raw materials in the catalyst preparation process to solve the problem of "ammonia nitrogen" and NO from the source. X pollution problem and reduce the cost of catalyst preparation.

[0003] Bulk hydrogenation catalysts are currently the catalysts with the highest hydrogenation activity centers. Bulk catalysts prepared by existing methods have smaller pore volumes and pore sizes, resulting in reactions on the catalyst surface that is inaccessible to reactant molecules. At the same time, the smaller pore volume and specific surface area cause the high content of active metals in the bulk catalyst to accumulate excessively on the catalyst surface, reducing the generation of active phases, lowering the activity of the catalyst, and also affecting the utilization rate of the active metals in the catalyst, thereby increasing the cost of using the catalyst.

[0004] The use of impregnation and kneading methods to prepare catalysts results in high catalyst preparation costs and large wastewater treatment costs because relatively low-priced sodium metal salt raw materials cannot be used. The coprecipitation method can use relatively low-priced sodium raw materials to prepare catalysts, which greatly reduces the catalyst preparation costs and wastewater treatment costs. However, the introduction of a large number of sodium ions makes it difficult to remove sodium ions from the catalyst. Even if the number of washings is increased (the increase in the number of washings will reduce the crushing strength of the catalyst), only the sodium ions on the surface of the catalyst can be removed. A large number of sodium ions still exist in the precipitated material. The residual sodium ions lead to poor adhesion of the material. The sodium ions that are not removed are not conducive to the formation of the catalyst pore structure, resulting in a small pore volume and pore size of the catalyst.

[0005] The existing co-precipitation method mostly uses ammonia water as a precipitant and nitrogen-containing soluble salts as raw materials. The distribution of hydrogenation active metals and the interaction between different hydrogenation active metals are improved by changing the precipitation method and gelation conditions. However, it does not solve the problems of small pore volume and specific surface area of ​​bulk catalysts, small pore size of catalysts (pore size distribution is mainly concentrated below 8nm), large metal oxide particles in catalysts, and "ammonia nitrogen" and NO in catalyst preparation. X There are many problems such as pollution and high cost. Especially when using cheaper sodium-containing raw materials, the gel-forming materials are loose and difficult to shape, and the catalyst has many small pores.

[0006] CN106179474B discloses a high-activity bulk hydroprocessing catalyst and a preparation method thereof. A two-step method of positive addition and parallel flow is adopted to prepare a precipitate containing W, Ni and Mo, and a microporous and mesoporous composite molecular sieve is added. The catalyst has a high surface active metal content, a more uniform active metal dispersion, good coordination between active metals, and a high active metal utilization rate. At the same time, the catalyst has a reasonable pore structure, high mechanical strength, and high hydrodesulfurization and hydrodenitrogenation activity. The catalyst prepared by this method contains a molecular sieve, and a strong acidity can improve the ultra-deep desulfurization activity of the catalyst, but a cracking reaction occurs, which reduces the yield of the diesel product.

[0007] CN102451706A discloses a method for preparing a hydrogenation catalyst composition, which uses a sodium aluminate solution, a mixed solution containing Ni and W component salts and CO2 gas for parallel flow reaction to generate a precipitate. CN110038581A discloses a method for preparing a hydrogenation refining catalyst. The hydrogenation refining catalyst is prepared by two-step precipitation, using sodium tungstate alkaline solution and sodium molybdate alkaline solution as precipitants for precipitation, respectively. Both methods use a large amount of sodium ion-containing salt as raw material for precipitation reaction, but the precipitate generated by this method contains a certain amount of sodium ions, the metal oxide particles are relatively large, and the residual sodium ions lead to poor adhesion of the material. The residual sodium ions also make the pore volume and specific surface area of ​​the catalyst small.

[0008] CN106513006A discloses a method for preparing a bulk phase hydrorefining catalyst, which comprises: pre-dispersing a Ni-containing compound with deionized water under an ultrasonic environment, then adding a Mo-containing compound to form a Ni-Mo fine grain structure, then adding a W-containing compound and a complexing agent for hydrothermal reaction, and then kneading and extruding the obtained active component powder with aluminum hydroxide dry glue, drying and calcining to obtain a catalyst. The catalyst prepared by the method of the present invention has uniform dispersion between different active phase grains, W source is embedded in the Ni-Mo skeleton structure, Ni-W active phase is easily wrapped by Ni-Mo active phase at the microscopic level, and is not an oxide core-shell structure at the macroscopic level, the pore volume is small, the effective active phase is not much, the metal oxide particles are large, and the removal efficiency of complex sulfur-containing compounds with high nitrogen content is limited. Summary of the invention

[0009] In view of the shortcomings of the prior art, the present invention provides a method for preparing a core-shell structure phase hydrorefining catalyst. The method has low preparation cost and a clean and pollution-free preparation process. The prepared catalyst has a core-shell structure, a large pore volume and a large pore size, and has high hydrodesulfurization and hydrodenitrogenation reaction performance in processes such as distillate oil hydrodesulfurization and denitrification, and is particularly suitable for treating inferior distillate oil raw materials.

[0010] The preparation method of the core-shell structure phase hydrorefining catalyst of the present invention comprises the following contents:

[0011] (1) subjecting a first precipitant, a sodium molybdate solution and a solution containing Ni and Si to a first gelling reaction, subjecting the reaction to a first aging to obtain a first slurry containing Ni, Si and Mo, filtering to obtain a filter cake, treating the filter cake with a mixed aqueous solution of an aluminum salt and an organic alcohol, and then stirring to obtain a mixed slurry containing Ni, Si, Mo, Al and an organic alcohol;

[0012] (2) adding the Ni-containing solution, the sodium tungstate solution, the second precipitant and the mixed slurry obtained in step (1) into a reactor containing water and an oily liquid in parallel to carry out a second gelling reaction, and then subjecting the reaction to a second aging to generate a second slurry;

[0013] (3) aging the second slurry, separating the solid from the liquid after aging, and drying and molding the solid phase to obtain a molded product;

[0014] (4) soaking the molded product in an organic acid solution of a carboxylic acid polymer and / or an organic phosphonic acid compound, desalting the soaked molded product, washing, drying and calcining the product to obtain a core-shell structure phase hydrogenation refining catalyst.

[0015] Furthermore, in the solution containing Ni and Si in step (1), the weight concentration of Ni calculated as NiO is 5-120 g / L, preferably 10-110 g / L, and the weight concentration of Si calculated as SiO2 is 2-80 g / L, preferably 4-70 g / L. When preparing the solution containing Ni and Si, the nickel source generally used is one or more of nickel sulfate, nickel nitrate, and nickel chloride, and the silicon source is one or more of water glass and silica sol.

[0016] Furthermore, in the sodium molybdate solution in step (1), the weight concentration of Mo in terms of MoO3 is 5 to 110 g / L, preferably 10 to 100 g / L.

[0017] Furthermore, the first precipitant described in step (1) can be an aqueous solution of an alkaline compound that does not contain nitrogen, preferably sodium hydroxide. The weight concentration of the first precipitant is 5% to 30%. Those skilled in the art can determine the amount of the first precipitant according to actual needs.

[0018] Furthermore, the conditions of the first gelling reaction in step (1) are as follows: the reaction temperature is 30-90°C, preferably 40-85°C, the pH value is controlled to be 7.0-11.0, preferably 7.2-10.0, and the gelling time is 0.2-2.5 hours, preferably 0.3-2.0 hours.

[0019] Furthermore, the first aging conditions in step (1) are as follows: the aging temperature is 60-90°C, preferably 65-85°C, the pH value during aging is controlled to be 7.0-11.0, preferably 7.2-10.5, and the aging time is 0.3-2.5 hours, preferably 0.5-2.0 hours.

[0020] Furthermore, in step (1), the weight of the introduced Ni accounts for 30% to 80% of the total Ni weight in the hydrotreating catalyst obtained in step (4), preferably 35% to 78%. In step (2), the weight of the introduced Ni accounts for 20% to 70% of the total Ni weight in the hydrotreating catalyst obtained in step (4), preferably 22% to 65%.

[0021] Furthermore, in step (1), the process of treating with a mixed aqueous solution of aluminum salt and organic alcohol is as follows: slurrying and mixing the mixed aqueous solution of aluminum salt and organic alcohol with the filter cake; the treatment conditions are as follows: temperature 0 to 30°C, preferably 5 to 28°C, time 1 to 16 hours, preferably 2 to 12 hours; the volume ratio of the mixed aqueous solution of aluminum salt and organic alcohol to the filter cake is 1.2:1 to 7:1, preferably 1.5:1 to 6:1; in the mixed aqueous solution of aluminum salt and organic alcohol, the weight concentration of aluminum salt in terms of Al2O3 is 5 to 100 g / L, preferably 7 to 90 g / L. The molar ratio of the amount of organic alcohol added to the amount of Mo in the sodium molybdate solution in step (1) is 0.1 to 3.0, preferably 0.3 to 2.8.

[0022] Further, the aluminum salt is one or more of aluminum chloride, aluminum nitrate, and aluminum sulfate; the organic alcohol is selected from one or more of aliphatic alcohols with carbon numbers of C2 to C5 and diols with carbon numbers of C2 to C10; further selected from one or more of ethanol, isopropanol, butanol, pentanol, ethylene glycol, propylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, trimethylene glycol, triethylene glycol, tributylene glycol, tetraethylene glycol, diethylene methyl glycol, diethylene ethyl glycol, diethylene propyl glycol, or diethylene butyl glycol; more preferably one or more of ethanol, isopropanol, butanol, ethylene glycol, propylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, tributylene glycol, tetraethylene glycol, diethylene ethyl glycol, or diethylene butyl glycol.

[0023] Furthermore, in the Ni-containing solution of step (2), the weight concentration of Ni in terms of NiO is 5 to 110 g / L, preferably 10 to 100 g / L.

[0024] Furthermore, in the sodium tungstate solution of step (2), the weight concentration of W in terms of WO3 is 4-140 g / L, preferably 6-120 g / L; in step (2), when preparing the Ni-containing solution, the nickel source generally used is one or more of nickel sulfate, nickel nitrate, and nickel chloride.

[0025] Furthermore, the second precipitant in step (2) is an alkaline precipitant, preferably an aqueous solution of sodium carbonate and / or sodium bicarbonate. The weight concentration of the second precipitant is 5% to 40%. The amount of the second precipitant can be determined by those skilled in the art according to actual needs.

[0026] Furthermore, the water added in step (2) is deionized water, and the volume ratio of the added water to the volume of the first slurry obtained in step (1) is 0.1:1 to 3:1.

[0027] Furthermore, the oily liquid in step (2) is unsaturated higher fatty acid glyceride (vegetable oil), preferably one or more of peanut oil, rapeseed oil, cottonseed oil, sunflower oil, soybean oil, corn oil, tea oil, and olive oil. The volume ratio of the oily liquid to water is 1:60 to 1:4, preferably 1:40 to 1:6.

[0028] Further, the conditions of the second gelling reaction of step (2) are as follows: the reaction temperature is 30-90°C, preferably 40-85°C, the pH value is initially controlled to be 10.0-14.0, preferably 10.5-13.5, the final pH value is 7.0-8.5, preferably 7.2-8.3, and the gelling reaction time is 0.5-6.0 hours, preferably 0.6-5.0 hours. Preferably, the pH value can be adjusted from the initial value to the final pH value by a stepwise downward adjustment method, and the stepwise downward adjustment method is to adjust the pH value to the desired value of the time, and keep the pH value of the reaction slurry constant until the next downward adjustment begins, and the number of downward adjustments is 2-10 times, preferably 2-8 times. Preferably, it is preferably kept constant for 0.1-1.2 hours after each downward adjustment. The amplitude of each downward adjustment can be the same or different, and it is preferred that the amplitude of the pH reduction in the current downward adjustment is equal to or less than the amplitude of the pH reduction in the previous downward adjustment. The time used for each downward adjustment process is from the start of the current downward adjustment to the start of the next downward adjustment, and further, is the sum of the time used for each pH value downward adjustment and the time when the pH value is constant. The time used for each downward adjustment process can be the same or different, and preferably the same time.

[0029] Furthermore, the second aging conditions in step (2) are as follows: aging temperature is 40-90° C., aging time is 1-5 hours, and pH value is 7.0-11.0. The aging is generally carried out under stirring conditions.

[0030] The aging conditions in step (2) are preferably carried out as follows: the first step is normal pressure aging: the aging temperature is 30-90°C, preferably 40-80°C, the aging time is 1-6 hours, preferably 1.2-5 hours, and the pH value is 6.5-10.0, preferably 7.0-9.0; the second step is high pressure aging: the temperature is 100-195°C, preferably 100-190°C, the time is 0.1-3.5 hours, preferably 0.3-2.8 hours, the pressure is not less than 10 MPa, preferably 10-15 MPa, and the pH value is 10.0-13.0, preferably 10.0-12.5. In the above-mentioned aging process, the material phase structure has formed a regular body in the first step of aging, and in a closed environment, under the action of higher temperature and pressure, the material phase changes from a regular body to an irregular body formed by irregular flakes. This structural change causes the sodium ions inside the phase to transfer to the surface of the phase, which is more conducive to the next step of desalination treatment, and is also conducive to increasing the specific surface area of ​​the bulk catalyst, improving the pore structure, exposing more active metals on the catalyst surface, and generating more hydrogenation active centers on the catalyst surface.

[0031] Furthermore, the solid-liquid separation in step (3) is generally carried out by filtration, centrifugation, etc.

[0032] Furthermore, the drying temperature in step (3) is 50 to 140° C., and the drying time is 0.5 to 24 hours.

[0033] Furthermore, the molding process described in step (3) is well known in the field of catalyst preparation. During the extrusion molding process, an extrusion aid and a peptizing agent are generally added. The extrusion aid can be one or more of sesbania powder, carbon black, graphite powder or cellulose, etc. The peptizing agent is generally an acid solution containing one or more of hydrochloric acid, sulfuric acid, acetic acid, etc. The amount of the extrusion aid accounts for 1wt% to 10wt% of the total material dry basis. The catalyst of the present invention can be prepared into the shape of flakes, spheres, cylindrical strips and special-shaped strips (three-leaf clover, four-leaf clover) as needed.

[0034] Furthermore, the water content in the organic acid solution of the carboxylic acid polymer and / or the organic phosphonic acid compound in step (4) is adjusted according to the volume of the catalyst to be soaked, so that the catalyst is fully soaked.

[0035] Furthermore, the carboxylic acid polymer in step (4) has a molecular weight of 400 to 5000 and is selected from one or more of polyacrylic acid, polymethacrylic acid, polymaleic acid, polyaspartic acid, polyepoxysuccinic acid, acrylic acid-hydroxypropyl acrylate copolymer and maleic acid-acrylic acid copolymer, preferably one or more of polyacrylic acid, polymethacrylic acid, polymaleic acid, polyaspartic acid or polyepoxysuccinic acid.

[0036] Furthermore, the organic phosphonic acid compound is selected from one or more of hydroxyethylidene diphosphonic acid, polyol phosphonate, 2-hydroxyphosphonoacetic acid, and 1,2,4-tricarboxylic acid-2-phosphonobutane.

[0037] Furthermore, the organic acid is selected from carboxylic acids with a carbon number of C2 to C8, further selected from one or more of malic acid, citric acid, isocitric acid, tartaric acid, oxalic acid, succinic acid, salicylic acid, lactic acid, β-hydroxybutyric acid, maleic acid, glutaric acid, adipic acid, benzoic acid or malonic acid, preferably one or more of malic acid, citric acid, tartaric acid, oxalic acid, succinic acid, salicylic acid or maleic acid.

[0038] Furthermore, the molar ratio of the organic phosphonic acid compound and / or carboxylic acid polymer to the organic acid in step (4) is 0.6:1 to 6:1, preferably 0.7:1 to 5:1; the molar ratio of the total molar number of the organic phosphonic acid compound or / and carboxylic acid polymer and the organic acid to the molar ratio of W in the sodium tungstate solution is 0.8 to 6.0, preferably 1.0 to 5.0.

[0039] Furthermore, the liquid-to-solid volume ratio of the soaking in step (4) is 1.0 to 5.0, preferably 1.0 to 4.0; and the soaking time is 1.0 to 12.0 hours, preferably 1.5 to 10.0 hours.

[0040] Furthermore, the desalination treatment process described in step (4) is: first curing, and then washing to remove the salt precipitated on the surface of the molded product, the curing conditions are a temperature of 5 to 100°C, preferably a temperature of 10 to 90°C, and a time of 10 to 100 hours, preferably 24 to 90 hours.

[0041] Furthermore, the desalination treatment described in step (4) is preferably carried out in the following manner: the first stage is carried out at a temperature of 60 to 90° C. for curing for 5 to 60 hours, preferably 8 to 55 hours, so that hydrated sodium ions are precipitated and vacancies are retained; the second stage is carried out at a temperature of 10 to 30° C. for 1 to 48 hours, preferably 2 to 42 hours, to promote vacancy retention and shrinkage, thereby increasing the pore volume of the catalyst and providing good mechanical strength, and then washing to remove the precipitated salt. The washing process can use a solvent with good solubility for sodium salts, such as water and ethanol.

[0042] Furthermore, the washing, drying and roasting in step (4) can be carried out under conventional conditions in the art. The drying conditions are as follows: drying at 40-150°C for 1-48 hours; the roasting conditions are as follows: roasting at 350-650°C for 1-24 hours. Washing is generally carried out with deionized water or ethanol solution until neutral.

[0043] The bulk hydrotreating catalyst of the present invention comprises core-shell structured composite oxide particles, wherein the core phase is an amorphous composite oxide containing molybdenum, nickel and silicon, and the shell phase is an amorphous composite oxide containing tungsten, nickel and aluminum; the core phase is 20% to 90%, and the shell phase is 10% to 80%; the average particle size of the core-shell structured composite oxide particles is 7 to 12 nm; preferably, the particle size distribution of the catalyst particles is as follows: the number of particles with a particle size less than 7 nm accounts for 2% to 15% of the total number of particles, the number of particles with a particle size of 7 nm to 12 nm accounts for 66% to 88% of the total number of particles, and the number of particles with a particle size greater than 12 nm accounts for 3% to 21% of the total number of particles.

[0044] In the catalyst of the present invention, the molar ratio of molybdenum to nickel atoms in the core phase is 1:28-12:1, preferably 1:22-10:1, and the silicon content in terms of SiO2 accounts for 2%-38% of the mass of the hydrorefining catalyst, preferably 4%-36%.

[0045] In the catalyst of the present invention, the molar ratio of tungsten to nickel atoms in the shell phase is 1:22-8:1, preferably 1:20-5:1, and the aluminum content, calculated as Al2O3, accounts for 5%-36% of the mass of the hydrorefining catalyst, preferably 7%-34%.

[0046] In the catalyst of the present invention, the mass of NiO in the core phase accounts for 30% to 80% of the total mass of NiO in the hydrorefining catalyst, and the mass of NiO in the shell phase accounts for 20% to 70% of the total mass of NiO in the hydrorefining catalyst.

[0047] The Na2O content in the catalyst of the present invention is less than 0.12%, preferably less than 0.1%.

[0048] In the catalyst of the present invention, the properties of the hydrotreating catalyst are as follows: the specific surface area is 180~700m 2 / g, pore volume is 0.30~0.90mL / g. The pore size distribution of the bulk hydrorefining catalyst of the present invention is as follows: the pore volume occupied by pores with a diameter of less than 4nm accounts for 1%~10% of the total pore volume, the pore volume occupied by pores with a diameter of 4~10nm accounts for 12%~40% of the total pore volume, the pore volume occupied by pores with a diameter of 10~15nm accounts for 22%~56% of the total pore volume, and the pore volume of pores with a diameter of more than 15nm accounts for 18%~45% of the total pore volume; the preferred pore size distribution is as follows: the pore volume occupied by pores with a diameter of less than 4nm accounts for 2%~8% of the total pore volume, the pore volume occupied by pores with a diameter of 4~10nm accounts for 14%~36% of the total pore volume, the pore volume occupied by pores with a diameter of 10~15nm accounts for 24%~54% of the total pore volume, and the pore volume of pores with a diameter of more than 15nm accounts for 20%~42% of the total pore volume.

[0049] The bulk hydrofining catalyst of the present invention is used in the hydrofining reaction of inferior distillate oil, wherein the inferior distillate oil is catalytic diesel, coker diesel, mixed diesel (mixture of catalytic diesel, coker diesel and straight-run diesel, with the mass percentage of catalytic diesel greater than 30%) and vacuum distillate.

[0050] Furthermore, the conditions of the inferior diesel hydrorefining reaction are as follows: reaction temperature is 330-400°C, reaction pressure is 2.5-17MPa, hydrogen-oil volume ratio is 250:1-1200:1, liquid hourly volume space velocity is 0.3-5.0h -1 .

[0051] Compared with the prior art, the present invention has the following advantages:

[0052] (1) The hydrorefining catalyst of the present invention improves the distribution state of active metals at the nano level, that is, it is mainly composed of composite oxide particles containing molybdenum, nickel and silicon coated with composite oxide containing tungsten, nickel and aluminum. This coating structure is different from the structure at the macro level (such as millimeter level). The structure of the catalytic material is controlled at the micro level, so that the overall performance of the catalyst can be improved, the hydrodesulfurization performance of the catalyst is improved, and a certain amount of acidic centers are formed at the junction of the core-shell structure of the catalyst, so that the catalyst can eliminate steric hindrance while performing hydrodesulfurization reaction, while reducing the occurrence of side reactions such as excessive cracking. The hydrorefining catalyst of the present invention has many active centers, uniform dispersion, high utilization rate and good mechanical strength, and is suitable for the hydrorefining reaction of heavy distillate oil (such as diesel), especially conducive to deep hydrodesulfurization and denitrification, and can also avoid reducing the diesel yield.

[0053] (2) In the method of the present invention, a mixed slurry of tungsten, nickel and silicon composite oxide filter cakes treated with a mixed solution of aluminum salt and organic alcohol is first prepared, and then added to a reactor containing water and an oily liquid in parallel with a nickel-aluminum mixed solution, a sodium tungstate solution and a precipitant, and a second gelation is performed using a pH value decreasing gelation method, so that tungsten and nickel are uniformly and orderly precipitated on molybdenum-nickel grains, thereby forming tungsten-nickel-coated molybdenum-nickel nanoparticles with uniform particle size and good dispersion. The different active metals in these metal particles and the active metals and the carrier have good coordination effects, and the core-shell composite oxide particles have good dispersibility. The pH value decreasing gelation is conducive to the uniform generation of core-shell composite oxide particles. The core phase oxides generated by treating the tungsten, nickel and silicon composite oxide filter cakes with a mixed solution of aluminum salts and organic alcohols have a more regular shape, which further promotes the uniform particle size distribution of the core-shell composite oxide particles. At the same time, the method of adding aluminum during the second gelling reaction is adjusted to further evenly disperse the active metals in the shell phase of the core-shell composite oxide particles. At the same time, the dispersion of aluminum in the shell phase is promoted, which is beneficial to a more uniform dispersion of the acidic centers formed at the junction of the core-shell structure.

[0054] (3) In the method of the present invention, a low-cost catalyst is prepared by a clean method. Since a soluble sodium salt is used as a raw material, a large amount of sodium ions are contained in the precipitate after gelation. The presence of a large amount of sodium ions causes the catalyst to have a small pore volume and is difficult to form. The inventor retains the sodium salt in the material during the forming process, and then desalts the formed material to remove the precipitated sodium salt. In this process, due to the occupying effect of the sodium salt during the forming process, the vacancies after sodium removal are more conducive to the formation of the catalyst pore structure, the pore distribution moves toward the macropore direction, the pore volume and pore diameter of the catalyst increase, and the diffusion performance of the catalyst is improved, which solves the problem of the small pore volume and difficulty in forming of the catalyst when the prior art uses clean raw materials to prepare bulk catalysts. Before the desalting treatment, the formed material is soaked in a special organic acid solution, and the sodium salt in the formed material is easier to remove. In the desalting process of the present invention, the number of washing times in the conventional catalyst preparation process is reduced, and the amount of water is reduced. Through the comprehensive control of the preparation steps and preparation conditions, the core-shell composite oxide structure obtained by the present invention is more conducive to the desalting treatment of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is the TEM image of catalyst C obtained in Example 2. DETAILED DESCRIPTION

[0056] In the present invention, the specific surface area and pore volume are measured by low temperature liquid nitrogen adsorption method, and the mechanical strength is measured by lateral pressure method. The specific surface area, pore volume and pore size distribution are measured by ASAP-2405 BET nitrogen adsorption instrument; the crushing strength of the catalyst is measured by ZQJ-2 intelligent particle strength testing machine.

[0057] In the present invention, in the core-shell composite oxide particles, the metal content in the composite oxide in the core and the shell and the thickness of the shell are measured by TEM transmission electron microscope (Japan JSM-2100). Among them, the method for determining the metal content in the composite oxide in the core and the shell is as follows: the core-shell composite oxide particles are uniformly mixed with liquid epoxy resin, and then an appropriate amount of curing agent is added, and the mixture is heated and cured after being stirred evenly to form solid particles. The solid particles are cut into thin slices with a thickness of 5-20nm by an ultrathin slicer, and the obtained slices are placed in a transmission electron microscope for observation to find a core-shell structure (cross section) with a clear interface. The diameter of the electron beam is adjusted by a condenser so that its diameter basically covers the outline of the entire core-shell structure, and the energy spectrum EDS spectrum is collected to record the intensity of the main energy peak, which corresponds to the actual content of each element in the known feed and the energy peak intensity of each element. The electron beam diameter is adjusted so that it is smaller than or close to the core or shell size, and the metal content in the composite oxide in the core and the shell at this time is calculated according to the energy peak intensity corresponding to the element, compared with the peak intensity under full coverage and the corresponding actual value. In the core-shell structure, the shell thickness is identified and measured from the transmission electron microscope image, and the ratio of the shell thickness to the total core-shell thickness is the average value obtained by measuring 40 to 100 core-shell particles.

[0058] In the present invention, wt% refers to mass fraction, and v% refers to volume fraction.

[0059] Example 1

[0060] Nickel chloride and water glass are added to a dissolution tank 1 filled with deionized water to prepare a solution containing Ni and Si. The weight concentration of Ni in the Ni and Si solution is 28 g / L as NiO, and the weight concentration of SiO2 is 36 g / L. Nickel chloride is added to a dissolution tank 2 filled with deionized water to prepare a solution containing Ni and Si. The weight concentration of Ni in the Ni-containing solution is 24 g / L as NiO. Among them, the mass ratio of Ni in the Ni and Si solution used in the reaction of this embodiment to Ni in the Ni-containing solution used is 14:12. A solution containing Ni and Si is put into a reaction tank 1, and a sodium hydroxide solution (weight concentration of 12%) and a sodium molybdate solution (weight concentration of Mo calculated as MoO3 is 36 g / L) are dripped into the reaction tank 1 for a first gelling reaction. The gelling temperature is maintained at 62°C, the pH value is controlled at 7.8 at the end of the reaction, and the gelling time is controlled at 1.2 hours. After the reaction is completed, aging is carried out at a temperature of 78°C, and the aging pH value is controlled at 7.5 for 1.8 hours to obtain a first slurry. After obtaining the first slurry, the first slurry is filtered, and the obtained filter cake is slurried and mixed with a mixed solution of aluminum chloride and propylene glycol (weight concentration of Al calculated as Al2O3 is 36 g / L, and the molar ratio of propylene glycol to Mo in the sodium molybdate solution is 2.0), and treated at a temperature of 25°C for 6 hours. The volume ratio of the mixed aqueous solution of aluminum salt and propylene glycol to the filter cake is 2:1. After treatment, it is stirred evenly to obtain a mixed slurry containing Ni, Si, Mo, Al and propylene glycol. First, 800 mL of deionized water and 60 mL of rapeseed oil were added to the reaction tank 2, and then a 10 wt% sodium carbonate solution, a mixed slurry containing Ni, Si, Mo, Al and propylene glycol, a Ni-containing solution and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 40 g / L) were added to the reaction tank 2 for a second gelling reaction. The gelling temperature was maintained at 60°C, and the pH value was initially controlled to be 13.0. The pH value was adjusted down 6 times to adjust the final pH value to 7.6 at the end. The pH value was adjusted down to 0.9 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was kept constant for 10 minutes. After the second gelling reaction was completed, aging began. The aging temperature was 78°C, the pH value was controlled at 8.0, and the aging time was 2.5 hours to obtain the second slurry. The aged slurry was filtered, the filter cake was dried at 100°C for 7 hours, rolled, and extruded into a clover shape. Mix polyacrylic acid (molecular weight 3000) and citric acid, add deionized water to prepare an organic acid solution, the molar ratio of the sum of the moles of polyacrylic acid and citric acid to W in the sodium tungstate solution is 2.6, and the molar ratio of polyacrylic acid to citric acid is 2.0. Soak the molded product in the above organic acid solution, the volume ratio of the organic acid solution to the molded product is 1.2, and the soaking time is 5 hours. After soaking, take out the molded product and cure it at a temperature of 70°C for 50 hours, then reduce the temperature to 20°C and continue curing for 30 hours. Wash it with deionized water at room temperature until it is neutral.The wet strips were then dried at 100°C for 12.0 hours, and the dried material was calcined at 500°C for 4 hours to obtain Catalyst A. The composition and main properties of the catalyst are shown in Table 1.

[0061] Example 2

[0062] Nickel chloride and water glass are added to a dissolution tank 1 filled with deionized water to prepare a solution containing Ni and Si, wherein the weight concentration of Ni in the Ni and Si solution is 20 g / L as NiO, and the weight concentration of SiO2 is 40 g / L. Nickel chloride is added to a dissolution tank 2 filled with deionized water to prepare a solution containing Ni, wherein the weight concentration of Ni in the Ni-containing solution is 20 g / L as NiO. Among them, the mass ratio of Ni in the Ni and Si-containing solution used in the reaction of this embodiment to Ni in the Ni-containing solution used is 10:10. A solution containing Ni and Si is put into a reaction tank 1, and a sodium hydroxide solution (weight concentration of 12%) and a sodium molybdate solution (weight concentration of Mo calculated as MoO3 is 38 g / L) are dripped into the reaction tank 1 for a first gelling reaction. The gelling temperature is maintained at 55°C, the pH value is controlled at 8.4 at the end of the reaction, and the gelling time is controlled at 1.7 hours. After the reaction is completed, aging is carried out, the aging temperature is 82°C, the aging pH value is controlled at 8.4, and the aging is carried out for 1.5 hours. After obtaining the first slurry, the first slurry is filtered, and the obtained filter cake is slurried and mixed with a mixed solution of aluminum chloride and butanol (weight concentration of Al calculated as Al2O3 is 34 g / L, and the molar ratio of Mo in butanol and sodium molybdate solution is 2.3), and treated at a temperature of 25°C for 5 hours. The volume ratio of the mixed aqueous solution of aluminum salt and butanol to the filter cake is 2.2:1. After treatment, it is stirred evenly to obtain a mixed slurry containing Ni, Si, Mo, Al and butanol. First, 500 mL of deionized water and 50 mL of corn oil were added to the reaction tank 2, and then a sodium carbonate solution with a concentration of 11 wt%, a mixed slurry containing Ni, Si, Mo, Al and butanol, a solution containing Ni and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 48 g / L) were added to the reaction tank 2 for the second gelling reaction. The gelling temperature was maintained at 65 ° C, and the pH value was initially controlled to be 13.1. The pH value was adjusted down 7 times to adjust the final pH value to 7.5 at the end. The pH value was adjusted down to 0.8 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was kept constant for 13 minutes. After the second gelling reaction was completed, aging began, the aging temperature was 82 ° C, the pH value was controlled at 8.0, and the aging time was 3.0 hours to obtain the second slurry. The aged slurry was filtered, and the filter cake was dried for the first time, dried at 100 ° C for 10 hours, rolled, and extruded into a clover shape. Mix hydroxyethylidene diphosphonic acid and oxalic acid and add them to deionized water to prepare an organic acid solution. The molar ratio of the sum of the moles of hydroxyethylidene diphosphonic acid and oxalic acid to the mole of W in the sodium tungstate solution is 2.1, and the molar ratio of the sum of the moles of hydroxyethylidene diphosphonic acid to the mole of oxalic acid is 3.2. Soak the molded product in the above organic acid solution. The volume ratio of the organic acid solution to the molded product is 1.1, and the soaking time is 6.5 hours. After soaking, take out the molded product and cure it at a temperature of 80°C for 48 hours, then reduce the temperature to 23°C and continue curing for 36 hours. Wash it with deionized water at room temperature until it is neutral.The wet strips were then dried at 100°C for 10.0 hours, and the dried material was calcined at 550°C for 4 hours to obtain catalyst B. The catalyst composition and main properties are shown in Table 1.

[0063] Example 3

[0064] Nickel chloride and water glass are added to a dissolution tank 1 filled with deionized water to prepare a solution containing Ni and Si. The weight concentration of Ni in the Ni and Si solution is 40 g / L as NiO, and the weight concentration of SiO2 is 44 g / L. Nickel chloride is added to a dissolution tank 2 filled with deionized water to prepare a solution containing Ni. The weight concentration of Ni in the Ni-containing solution is 24 g / L as NiO. The mass ratio of Ni in the Ni and Si-containing solution used in the reaction of this embodiment to Ni in the Ni-containing solution used is 20:12. A solution containing Ni and Si is put into a reaction tank 1, and a sodium hydroxide solution (weight concentration of 10%) and a sodium molybdate solution (weight concentration of Mo calculated as MoO3 is 36 g / L) are dripped into the reaction tank 1 for a first gelling reaction. The gelling temperature is maintained at 65°C, the pH value is controlled at 8.6 at the end of the reaction, and the gelling time is controlled at 1.0 hour. After the reaction is completed, aging is carried out, the aging temperature is 78°C, the aging pH value is controlled at 8.2, and the aging is carried out for 1.8 hours. After obtaining the first slurry, the first slurry is filtered, and the obtained filter cake is slurried and mixed with a mixed solution of aluminum chloride and ethylene glycol (weight concentration of Al calculated as Al2O3 is 28 g / L, and the molar ratio of ethylene glycol to Mo in the sodium molybdate solution is 2.8), and treated at a temperature of 28°C for 6 hours. The volume ratio of the mixed aqueous solution of aluminum salt and ethylene glycol to the filter cake is 2.8:1. After treatment, it is stirred evenly to obtain a mixed slurry containing Ni, Si, Mo, Al and ethylene glycol. First, 1000mL of deionized water and 90mL of peanut oil were added to the reaction tank 2, and then a 14wt% sodium carbonate solution, a mixed slurry containing Ni, Si, Mo, Al and ethylene glycol, a Ni-containing solution and a sodium tungstate solution (the weight concentration of W calculated as WO3 is 28g / L) were added to the reaction tank 2 in parallel for a second gelation reaction. The gelation temperature was maintained at 60°C, and the pH value was initially controlled to be 12.8. The pH value was adjusted down 6 times to adjust the final pH value to 8.0 at the end, and the pH value was adjusted down by 0.8 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was kept constant for 14 minutes. After the second gelation reaction was completed, aging began, the aging temperature was 78°C, and the aging pH value was controlled at 8.5. After aging for 2.8 hours, the precipitate slurry continued to be aged under high pressure, with a pressure of 13.6MPa, an aging temperature of 180°C, an aging time of 1.5 hours, and an aging pH value of 12.3 to obtain a second slurry. The aged slurry was filtered, the filter cake was dried at 120°C for 8 hours, rolled, and extruded into a clover-shaped strip. Polyacrylic acid and salicylic acid were mixed, and purified water was added to prepare an organic auxiliary solution. The molar ratio of the sum of the moles of polyacrylic acid and salicylic acid to the molar ratio of W in the sodium tungstate solution was 3.2, and the molar ratio of polyacrylic acid to salicylic acid was 3.0. The molded product was soaked in the above organic acid solution. The volume ratio of the organic acid solution to the molded product was 1.2, and the soaking time was 7.5 hours.After soaking, the molded product was taken out and cured for 72 hours at 76°C. It was washed with deionized water at room temperature until neutral. The wet strips were then dried at 80°C for 12.0 hours, and the dried material was calcined at 520°C for 5 hours to obtain catalyst C. The catalyst composition and main properties are shown in Table 1.

[0065] Example 4

[0066] Nickel chloride and water glass are added to a dissolution tank 1 filled with deionized water to prepare a solution containing Ni and Si, wherein the weight concentration of Ni in the Ni and Si solution is 30 g / L as NiO, and the weight concentration of SiO2 is 32 g / L. Nickel chloride is added to a dissolution tank 2 filled with deionized water to prepare a solution containing Ni, wherein the weight concentration of Ni in the Ni-containing solution is 20 g / L as NiO. Among them, the mass ratio of Ni in the Ni and Si-containing solution used in the reaction of this embodiment to Ni in the Ni-containing solution used is 15:10. A solution containing Ni and Si is put into a reaction tank 1, and a sodium hydroxide solution (weight concentration of 13%) and a sodium molybdate solution (weight concentration of Mo calculated as MoO3 is 32 g / L) are dripped into the reaction tank 1 for a first gelling reaction. The gelling temperature is maintained at 70°C, the pH value is controlled at 8.2 at the end of the reaction, and the gelling time is controlled at 0.9 hour. After the reaction is completed, aging is carried out, the aging temperature is 79°C, the aging pH value is controlled at 8.4, and the aging is carried out for 1.6 hours. After obtaining the first slurry, the first slurry is filtered, and the obtained filter cake is slurried and mixed with a mixed solution of aluminum chloride and propylene glycol (weight concentration of Al calculated as Al2O3 is 42 g / L, and the molar ratio of propylene glycol to Mo in the sodium molybdate solution is 3.0), and treated at a temperature of 18°C ​​for 5 hours. The volume ratio of the mixed aqueous solution of aluminum salt and propylene glycol to the filter cake is 3.1:1. After treatment, it is stirred evenly to obtain a mixed slurry containing Ni, Si, Mo, Al and propylene glycol. First, 800 mL of deionized water and 70 mL of sunflower oil were added to the reaction tank 2, and then a sodium carbonate solution with a concentration of 13 wt%, a mixed slurry containing Ni, Si, Mo, Al and propylene glycol, a solution containing Ni and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 44 g / L) were added to the reaction tank 2 for a second gelling reaction. The gelling temperature was maintained at 75°C, and the pH value was initially controlled to be 13.3. The pH value was adjusted down 5 times to adjust the final pH value to 7.8 at the end, and the pH value was adjusted to 1.1 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was kept constant for 12 minutes. After the second gelling reaction was completed, aging began, the aging temperature was 84°C, the aging pH value was controlled at 8.4, and the aging was 2.6 hours. Then, the precipitate slurry continued to be aged under high pressure, the pressure was 13.8 MPa, the aging temperature was 180°C, the aging time was 1.4 hours, and the aging pH value was 12.0. The second slurry was obtained. The aged slurry was filtered, the filter cake was dried at 90°C for 10 hours, rolled, and extruded into a clover-shaped strip. Hydroxyethylidene diphosphonic acid, polymaleic acid (molecular weight 450) and tartaric acid were mixed, and deionized water was added to prepare an organic acid solution. The molar ratio of the sum of the moles of hydroxyethylidene diphosphonic acid, polymaleic acid (molecular weight 450) and tartaric acid to W in the sodium tungstate solution was 2.4, and the molar ratio of the sum of the moles of hydroxyethylidene diphosphonic acid and polymaleic acid (molecular weight 450) to tartaric acid was 3.2.The molded product was soaked in the above organic acid solution, the volume ratio of the organic acid solution to the molded product was 1.2, and the soaking time was 7 hours. After soaking, the molded product was taken out and cured at 70°C for 45 hours, then the temperature was reduced to 24°C and continued to cure for 35 hours. It was washed with deionized water at room temperature until neutral. The wet strip was then dried at 120°C for 7.0 hours, and the dried material was roasted at 520°C for 4 hours to obtain catalyst D. The catalyst composition and main properties are shown in Table 1.

[0067] Comparative Example 1

[0068] The reference agent E having the same catalyst composition as that of Example 1 was prepared, and the specific process was as follows:

[0069] According to the catalyst composition of Example 1, nickel chloride, aluminum chloride and water glass are dissolved in deionized water to prepare a mixed solution, wherein the weight concentration of Ni in terms of NiO is 52g / L, the weight concentration of Al in terms of Al2O3 is 36g / L, and the weight concentration of SiO2 is 36g / L. 500mL of deionized water is added to a reaction tank, and a 10wt% NaOH solution, a sodium molybdate solution (the weight concentration of Mo in terms of MoO3 is 36g / L), a sodium tungstate solution (the weight concentration of W in terms of WO3 is 40g / L) and a mixed solution are added to the reaction tank in parallel to form a gel, and the gelling temperature is maintained at 62°C, the pH value is controlled at 7.8 at the end, and the gelling time is controlled at 1.2 hours to generate a nickel- and tungsten-containing precipitate slurry. Then, aging is performed, the aging time is 2.0 hours, the aging temperature is 78°C, the pH value is controlled at 7.5 during aging, and the reaction slurry is filtered after the aging is completed, and the filter cake is dried at 100°C for 7 hours, rolled, and extruded into strips. The molded product was washed with deionized water at room temperature, but no molded product was obtained after washing. The powder was dried at 100°C for 12 hours and calcined at 500°C for 4 hours to obtain catalyst E. The composition and main properties of the catalyst are shown in Table 1.

[0070] Comparative Example 2

[0071] According to the method disclosed in CN102049295A, a reference agent F having a catalyst composition similar to that of Example 1 was prepared. The specific process is as follows:

[0072] After adding 1000mL of deionized water into the dissolving tank, nickel chloride, ammonium metatungstate and aluminum chloride solution are added in sequence, and mixed solution is prepared after uniform stirring. Among them, the weight concentration of Ni in terms of NiO is 52g / L, the weight concentration of W in terms of WO3 is 40g / L, and the weight concentration of Al in terms of Al2O3 is 54g / L. Take 160g of ammonium bicarbonate to prepare an aqueous solution with a molar concentration of 2.5mol / L. Then the mixed solution, ammonium bicarbonate aqueous solution and precipitant 10% ammonia water are added to the reaction tank filled with deionized water at the same time and flow to form gel. The gel pH value is 7.8 and the gel temperature is 62°C. After the gel is completed, add the slurry containing SAPO-11 molecular sieve and age for 2 hours at an aging temperature of 78°C. The pH value is controlled at 7.5 during aging. After aging, the filter cake was filtered, 600 mL of deionized water and 36 g of molybdenum trioxide were added, slurried and stirred evenly, and filtered. The filter cake was dried at 100°C for 7 hours, then extruded into strips, washed with deionized water until neutral, and the wet strips were dried at 100°C for 12 hours and calcined at 500°C for 4 hours to obtain the final catalyst F. The composition and main properties are shown in Table 1.

[0073] The SAPO-11 molecular sieve used in the comparative example is the one used in CN102049295A, which can be synthesized by conventional methods, such as hydrothermal crystallization method, and has the following properties: SiO2 / Al2O3 molar ratio of 0.85, infrared acid content of 0.9 mmol / g, pore volume of 0.24 mL / g, specific surface area of ​​250 m 2 / g, particle size is 450nm and crystallinity is 85%.

[0074] Comparative Example 3

[0075] Reference agent G was prepared according to the preparation method of Example 1 (no grease was added to the gelling tank during the second step of gelling) and the catalyst composition.

[0076] Nickel chloride and water glass are added to a dissolution tank 1 filled with deionized water to prepare a solution containing Ni and Si. The weight concentration of Ni in the Ni and Si solution is 28 g / L as NiO, and the weight concentration of SiO2 is 36 g / L. Nickel chloride is added to a dissolution tank 2 filled with deionized water to prepare a solution containing Ni and Si. The weight concentration of Ni in the Ni-containing solution is 24 g / L as NiO. Among them, the mass ratio of Ni in the Ni and Si solution used in the reaction of this embodiment to Ni in the Ni-containing solution used is 14:12. A solution containing Ni and Si is put into a reaction tank 1, and a sodium hydroxide solution (weight concentration of 12%) and a sodium molybdate solution (weight concentration of Mo calculated as MoO3 is 36 g / L) are dripped into the reaction tank 1 for a first gelling reaction. The gelling temperature is maintained at 62°C, the pH value is controlled at 7.8 at the end of the reaction, and the gelling time is controlled at 1.2 hours. After the reaction is completed, aging is carried out at a temperature of 78°C, and the aging pH value is controlled at 7.5 for 1.8 hours to obtain a first slurry. After obtaining the first slurry, the first slurry is filtered, and the obtained filter cake is mixed with a mixed solution of aluminum chloride and propylene glycol (weight concentration of Al calculated as Al2O3 is 36 g / L, and the molar ratio of propylene glycol to Mo in the sodium molybdate solution is 2.0) by beating and mixing, and treated at a temperature of 25°C for 6 hours. The volume ratio of the mixed aqueous solution of aluminum salt and propylene glycol to the filter cake is 2:1. After treatment, the mixture is stirred evenly to obtain a mixed slurry containing Ni, Si, Mo, Al and propylene glycol. First, 800 mL of deionized water was added to the reaction tank 2, and then a 10 wt% sodium carbonate solution, a mixed slurry containing Ni, Si, Mo, Al and propylene glycol, a Ni-containing solution and a sodium tungstate solution (W weight concentration in terms of WO3 is 40 g / L) were added to the reaction tank 2 for the second gelling reaction. The gelling temperature was maintained at 60 ° C, and the pH value was initially controlled to be 13.0. The pH value was adjusted down 6 times to adjust the final pH value to 7.6 at the end. The pH value was adjusted down to 0.9 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was kept constant for 10 minutes. After the second gelling reaction was completed, aging began. The aging temperature was 78 ° C, the pH value was controlled at 8.0, and the aging time was 2.5 hours to obtain the second slurry. The aged slurry was filtered, the filter cake was dried at 100 ° C for 7 hours, rolled, and extruded into a clover shape. Mix polyacrylic acid (molecular weight 3000) and citric acid, add deionized water to prepare an organic acid solution, the molar ratio of the sum of the moles of polyacrylic acid and citric acid to W in the sodium tungstate solution is 2.0, and the molar ratio of polyacrylic acid to citric acid is 2.0. Soak the molded product in the above organic acid solution, the volume ratio of the organic acid solution to the molded product is 1.2, and the soaking time is 5 hours. After soaking, take out the molded product and cure it at 70°C for 50 hours, then reduce the temperature to 20°C and continue curing for 30 hours. Wash it with deionized water at room temperature until it is neutral.The wet strips were then dried at 100°C for 12.0 hours, and the dried material was calcined at 500°C for 4 hours to obtain Catalyst G. The composition and main properties of the catalyst are shown in Table 1.

[0077] Comparative Example 4

[0078] Reference agent H was prepared according to the preparation method of Example 1 (no silicon was added when preparing mixed solution A).

[0079] The nickel chloride solution and the aluminum chloride solution are respectively added to the dissolution tank 1 filled with deionized water to prepare a solution containing Ni and Al, wherein the weight concentration of Ni in the Ni and Al solutions is 28 g / L as NiO, and the weight concentration of Al in Al2O3 is 36 g / L. The nickel chloride solution is added to the dissolution tank 2 filled with deionized water to prepare a solution containing Ni, wherein the weight concentration of Ni in the Ni-containing solution is 24 g / L as NiO. Among them, the mass ratio of Ni in the Ni and Al-containing solution used in the reaction of this embodiment to Ni in the Ni-containing solution used is 14:12. A solution containing Ni and Al is put into a reaction tank 1, and a sodium hydroxide solution (weight concentration of 12%) and a sodium molybdate solution (weight concentration of Mo calculated as MoO3 is 36 g / L) are dripped into the reaction tank 1 for a first gelling reaction. The gelling temperature is maintained at 62°C, the pH value is controlled at 7.8 at the end of the reaction, and the gelling time is controlled at 1.2 hours. After the reaction is completed, aging is carried out at a temperature of 78°C, and the aging pH value is controlled at 7.5 for 1.8 hours to obtain a first slurry. After obtaining the first slurry, the first slurry is filtered, and the obtained filter cake is mixed with a mixed solution of aluminum chloride and propylene glycol (weight concentration of Al calculated as Al2O3 is 36 g / L, and the molar ratio of propylene glycol to Mo in the sodium molybdate solution is 2.0) by beating and mixing, and treated at a temperature of 25°C for 6 hours. The volume ratio of the mixed aqueous solution of aluminum salt and propylene glycol to the filter cake is 2:1. After treatment, it is stirred evenly to obtain a mixed slurry containing Ni, Mo, Al and propylene glycol. First, 800 mL of deionized water and 60 mL of rapeseed oil were added to the reaction tank 2, and then a 10 wt% sodium carbonate solution, a mixed slurry containing Ni, Mo, Al and propylene glycol, a Ni-containing solution and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 40 g / L) were added to the reaction tank 2 for a second gelling reaction. The gelling temperature was maintained at 60 ° C, and the pH value was initially controlled to be 13.0. The pH value was adjusted down 6 times to adjust the final pH value to 7.6 at the end. The pH value was adjusted down to 0.9 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was kept constant for 10 minutes. After the second gelling reaction was completed, aging began. The aging temperature was 78 ° C, the pH value was controlled at 8.0, and the aging time was 2.5 hours to obtain the second slurry. The aged slurry was filtered, the filter cake was dried at 100 ° C for 7 hours, rolled, and extruded into a clover shape. Mix polyacrylic acid (molecular weight 3000) and citric acid, add deionized water to prepare an organic acid solution, the molar ratio of the sum of the moles of polyacrylic acid and citric acid to W in the sodium tungstate solution is 2.0, and the molar ratio of polyacrylic acid to citric acid is 2.0. Soak the molded product in the above organic acid solution, the volume ratio of the organic acid solution to the molded product is 1.2, and the soaking time is 5 hours. After soaking, take out the molded product and cure it at 70°C for 50 hours, then reduce the temperature to 20°C and continue curing for 30 hours. Wash it with deionized water at room temperature until it is neutral.The wet strips were then dried at 100°C for 12.0 hours, and the dried material was calcined at 500°C for 4 hours to obtain catalyst H. The composition and main properties of the catalyst are shown in Table 1.

[0080] Comparative Example 5

[0081] According to the method of Example 1, Catalyst I was prepared according to the component content ratio of Catalyst A in Table 1, and the formed strips were not subjected to desalination treatment.

[0082] Nickel chloride and water glass are added to a dissolution tank 1 filled with deionized water to prepare a solution containing Ni and Si. The weight concentration of Ni in the Ni and Si solution is 28 g / L as NiO, and the weight concentration of SiO2 is 36 g / L. Nickel chloride is added to a dissolution tank 2 filled with deionized water to prepare a solution containing Ni and Si. The weight concentration of Ni in the Ni-containing solution is 24 g / L as NiO. Among them, the mass ratio of Ni in the Ni and Si solution used in the reaction of this embodiment to Ni in the Ni-containing solution used is 14:12. A solution containing Ni and Si is put into a reaction tank 1, and a sodium hydroxide solution (weight concentration of 12%) and a sodium molybdate solution (weight concentration of Mo calculated as MoO3 is 36 g / L) are dripped into the reaction tank 1 for a first gelling reaction. The gelling temperature is maintained at 62°C, the pH value is controlled at 7.8 at the end of the reaction, and the gelling time is controlled at 1.2 hours. After the reaction is completed, aging is carried out at a temperature of 78°C, and the aging pH value is controlled at 7.5 for 1.8 hours to obtain a first slurry. After obtaining the first slurry, the first slurry is filtered, and the obtained filter cake is mixed with a mixed solution of aluminum chloride and propylene glycol (weight concentration of Al calculated as Al2O3 is 36 g / L, and the molar ratio of propylene glycol to Mo in the sodium molybdate solution is 2.0) by beating and mixing, and treated at a temperature of 25°C for 6 hours. The volume ratio of the mixed aqueous solution of aluminum salt and propylene glycol to the filter cake is 2:1. After treatment, the mixture is stirred evenly to obtain a mixed slurry containing Ni, Si, Mo, Al and propylene glycol. First, 800 mL of deionized water and 60 mL of rapeseed oil were added to the reaction tank 2, and then a 10 wt% sodium carbonate solution, a mixed slurry containing Ni, Si, Mo, Al and propylene glycol, a Ni-containing solution and a sodium tungstate solution (the weight concentration of W in terms of WO3 is 40 g / L) were added to the reaction tank 2 for the second gelling reaction. The gelling temperature was maintained at 60 ° C, and the pH value was initially controlled to be 13.0. The pH value was adjusted down 6 times to adjust the final pH value to 7.6 at the end. The pH value was adjusted down to 0.9 each time. After each adjustment to the adjusted value, the adjusted pH value of the reaction slurry was kept constant for 10 minutes. After the second gelling reaction was completed, aging began. The aging temperature was 78 ° C, the pH value was controlled at 8.0, and the aging time was 2.5 hours to obtain the second slurry. The aged slurry was filtered, the filter cake was dried at 100 ° C for 7 hours, rolled, and extruded into a clover shape. It was washed with deionized water at room temperature, and no molded object was obtained after washing. The powder was calcined at 500°C for 4 hours to obtain Catalyst I. The composition and main properties of the catalyst are shown in Table 1.

[0083] Comparative Example 6

[0084] According to the preparation method disclosed in CN106513006A, a reference agent J having a catalyst composition similar to that of Example 1 of the present invention was prepared. The specific process is as follows:

[0085] Nickel carbonate and 300 ml of deionized water were uniformly mixed and added to a 1L high-pressure ultrasonic reactor. The ultrasonic frequency was set to 60 KHz, and the mixture was heated to 80°C. After being kept at this temperature for 1 hour, the ultrasonic frequency was reduced to 20 KHz, the system temperature was increased to 120°C, ammonium molybdate and 3 g of polyvinyl pyrrolidone were added, and then 10 ml of 25 wt% ammonia water was added dropwise to the system. After being kept at this temperature for 2 hours, the ultrasound was turned off, stirring was turned on, and the speed was 300 rpm. Ammonium metatungstate was added, and then citric acid was added until the pH of the system was 4.2. After being kept at this temperature for 2 hours, the heating was turned off, and the slurry was collected after the system was cooled to room temperature. The slurry was spray dried, and the inlet temperature and outlet temperature were controlled at about 200°C and 100°C, respectively. The obtained dry powder was roasted at 330°C in a muffle furnace for 3 hours to obtain the active component powder. The active component powder was mixed with aluminum hydroxide dry gel, and then a 10% dilute nitric acid aqueous solution was added for kneading and extrusion to obtain a strip. The strip was dried at 110°C for 10 h and calcined in a muffle furnace at 400°C for 5 h to obtain a reference agent J. The catalyst composition and main properties are shown in Table 1.

[0086] Comparative Example 7

[0087] According to the preparation method disclosed in CN1951558A, reference agent K was prepared as follows:

[0088] Add deionized water to the dissolving tank, add nickel chloride, ammonium metatungstate and aluminum chloride to dissolve, prepare acidic working solution A, the weight concentration of Ni in solution A is 74.8g / L in terms of NiO, the weight concentration of W in terms of WO3 is 48.6g / L, the weight concentration of Al in terms of Al2O3 is 44g / L, and the pH value of solution A is 1.8. Add 350mL of deionized water to the reaction tank, and the temperature rises to 62°C. Under stirring, add solution A and 10wt% ammonia water to the reaction tank in parallel to form gel, the gelling temperature is 62°C, the gelling time is 1 hour, and the pH value of the slurry during the gelling process is 8.5. After the gelling is completed, age for 2 hours, the aging temperature is 75°C, and the pH value is controlled at 7.6 during aging. Then filter, add 600mL of deionized water and 32.6g of molybdenum trioxide to the filter cake, beat and stir evenly, filter, dry the filter cake at 100°C for 7 hours, roll, and extrude into a cylindrical shape. The wet strips were washed with deionized water at room temperature until neutral. The wet strips were then dried at 100°C for 12 hours and calcined at 500°C for 4 hours to obtain catalyst K. The catalyst composition and main properties are shown in Table 1.

[0089] Example 5

[0090] This example is an activity evaluation experiment of the catalyst of the present invention, and is compared with the catalyst of the comparative example. From the physicochemical properties of the catalyst in Table 1, it can be seen that when the raw materials contain more sodium raw materials during the preparation process, the catalysts A, B, C of the present invention and the comparative catalysts F, G, H, J, K are used for washing (the comparative catalysts E and F are washed into powders without activity evaluation), and a comparative evaluation test is carried out on a 200mL small hydrogenation device. The mixed diesel (the weight ratio of straight-run diesel, coking diesel, and catalytic diesel is 28:20:52) is the test raw material. The process conditions for the catalyst activity evaluation are: hydrogen partial pressure of 6.4MPa, reaction temperature of 365°C, liquid hourly volume space velocity of 2.0h -1 , the volume ratio of hydrogen to oil is 500:1, and the main properties of the raw materials are shown in Table 4. The results of catalyst activity evaluation are shown in Table 5. The types of sulfides in the hydrorefined oil were detected by gas chromatography-atomic emission spectrometry detector (GC-AED), and the results are shown in Table 6.

[0091] It can be seen from Table 1 that when the catalyst of the present invention uses a relatively high sodium-containing raw material in the preparation process, the catalyst has good crushing strength after desalting and washing after molding, while without desalting, the molded catalyst strips become powder after washing.

[0092] It can be seen from the evaluation results that compared with the comparative example catalyst, the catalyst of the present invention shows high hydrodesulfurization activity when removing difficult-to-treat 4,6-DMDBT macromolecular sulfides, and has excellent ultra-deep hydrodesulfurization activity. At the same time, the diesel product has a good yield. When the activity evaluation reaction space velocity is increased, the catalyst of the present invention still has excellent ultra-deep desulfurization activity by increasing the reaction temperature. Compared with the evaluation results of the comparative example catalyst, the catalyst of the present invention effectively reduces the influence of thermodynamic equilibrium on the high-temperature hydrogenation pathway and has good temperature adaptability. The hydrorefining catalyst of the present invention has a large pore volume and specific surface area, and the pore distribution is mainly concentrated above 10nm. The catalyst of the present invention is used for processing light distillate oil, especially for processing inferior diesel fractions, and has excellent ultra-deep hydrodesulfurization and denitrification performance.

[0093] Table 1 Composition and properties of catalysts prepared in Examples and Comparative Examples

[0094] Catalyst No. A B C D NiO, wt% 26 20 32 25 <![CDATA[WO3,wt%]]> 20 24 14 22 <![CDATA[MoO3,wt%]]> 18 19 18 16 <![CDATA[SiO2,wt%]]> 18 20 22 16 <![CDATA[Al2O3,wt%]]> 18 17 14 21 <![CDATA[Na2O,%]]> 0.064 0.068 0.065 0.056 <![CDATA[Specific surface area, m 2 / g]]> 301 303 308 315 Pore ​​volume, mL / g 0.415 0.421 0.432 0.443 Pore ​​distribution <4nm 5.22 5.13 5.09 4.84 4nm~10nm 21.34 21.14 21.01 20.01 10nm~15nm 42.21 42.36 42.78 43.05 >15nm 31.23 31.37 31.12 32.11 Mechanical strength, N / mm 19.3 19.6 19.4 19.1

[0095] Table 1 (Continued) Composition and properties of catalysts prepared in Examples and Comparative Examples

[0096] Catalyst No. E F G H I J K NiO, wt% 26 26 26 26 26 26 37.4 <![CDATA[WO3,wt%]]> 20 20 20 20 20 20 24.3 <![CDATA[MoO3,wt%]]> 18 18 18 18 18 18 16.3 <![CDATA[SiO2,wt%]]> 18 4 18 - 18 - - <![CDATA[Al2O3,wt%]]> 18 28 18 36 18 36 22 <![CDATA[P2O5,wt%]]> - 4 - - - - - <![CDATA[Na2O,%]]> 0.34 0.14 0.096 0.068 0.44 0.13 0.13 <![CDATA[Specific surface area, m 2 / g]]> 142 199 267 299 239 283 174 Pore ​​volume, mL / g 0.232 0.252 0.379 0.410 0.349 0.385 0.301 Pore ​​distribution <4nm 62.81 22.82 10.16 5.86 17.62 38.21 46.87 4nm~10nm 30.52 71.44 33.31 21.71 41.34 48.61 40.72 10nm~15nm 4.37 4.50 38.43 42.41 27.21 7.28 8.26 >15nm 2.30 1.24 18.10 30.02 13.83 5.90 4.15 Mechanical strength, N / mm - 17.6 18.4 18.7 - 13.5 19.1

[0097] Table 2 The composition of the composite oxides in the core and shell of the catalysts obtained in each example (based on the mass of the catalyst)

[0098] Catalyst No. A B C D G H I Composite oxide composition in the core NiO, wt% 14 10 20 15 18 14 14 <![CDATA[MoO3,wt%]]> 18 19 18 16 14 18 18 <![CDATA[SiO2,wt%]]> 18 20 22 16 14 - 18 <![CDATA[WO3,wt%]]> - - - - 7 - - <![CDATA[Al2O3,wt%]]> - - - - 6 18 - Composite oxide composition in shell NiO, wt% 12 10 12 10 8 12 12 <![CDATA[WO3,wt%]]> 20 24 14 22 13 20 20 <![CDATA[Al2O3,wt%]]> 18 17 14 21 12 18 18 <![CDATA[MoO3,wt%]]> - - - - 4 - - <![CDATA[SiO2,wt%]]> - - - - 4 - -

[0099] Table 3 Average particle size and particle size distribution of the catalyst core-shell composite oxide particles obtained in each example

[0100] Catalyst No. A B C D E F Average particle size of core-shell composite oxide particles, nm 8.4. 8.6 8.4 8.3 33.6 23.8 Particle size distribution of core-shell composite oxide particles, % Particle size less than 7nm 5.14 5.32 5.08 5.01 3.32 4.05 Particle size is 7nm-12nm 83.43 83.05 83.75 83.94 16.13 23.81 Particle size greater than 12nm 11.43 11.63 11.17 11.05 80.55 72.14

[0101] Table 3 (Continued) Average particle size and particle size distribution of the catalyst core-shell composite oxide particles obtained in each example

[0102] Catalyst No. G H I J K Average particle size of core-shell composite oxide particles, nm 31.3 8.6 9.8 24.4 19.4 Particle size distribution of core-shell composite oxide particles, % Particle size less than 7nm 3.16 5.34 5.81 8.93 8.42 Particle size is 7nm-12nm 25.28 83.41 80.46 25.23 30.35 Particle size greater than 12nm 71.56 11.25 13.73 65.84 61.23

[0103] Table 4 Main properties of crude oil

[0104] project Analyze the results <![CDATA[Density (20 °C), g / cm 3 > 0.8897 Distillation range, ℃ 175-379 S, µg / g 13100 N, µg / g 922

[0105] Table 5 Catalysts and activity evaluation results

[0106] Catalyst No. A B C F G H J K <![CDATA[Generated oil density (20 °C), g / cm 3 > 0.8632 0.8634 0.8630 0.8656 0.8705 0.8646 0.8772 0.8707 S, µg / g 8.8 8.5 8.3 38.2 133.9 28.7 236.8 118.8 N, µg / g 4.3 4.0 3.8 16.4 69.4 11.4 112.8 62. 2 Diesel yield, % 99.1 99.1 99.2 86.6 98.7 99.0 98.3 98.9

[0107] Table 6 Content of different sulfides in hydrorefined oil

[0108] Catalyst No. A B C F G H J K Sulfur content in hydrorefined oil, µg / g 8.8 8.5 8.3 38.2 133.9 28.7 236.8 118.8 <![CDATA[C1-DBT,µg / g]]> 0 0 0 3.2 10.3 2.5 22.1 9.1 4- MDBT, µg / g 1.8 1.7 1.7 8.1 28.4 6.2 52.2 25.4 6-MDBT, µg / g 2.3 2.2 2.1 9.6 29.4 7.7 60.2 26.3 4,6-DMDBT, µg / g 4.7 4.6 4.6 17.3 65.8 12.3 102.3 58.0

Claims

1. A method for preparing a core-shell structure phase hydrorefining catalyst, characterized in that The method comprises the following contents: (1) subjecting a first precipitant, a sodium molybdate solution and a solution containing Ni and Si to a first gelling reaction, subjecting the first precipitant to a first aging reaction after the reaction to obtain a first slurry containing Ni, Si and Mo, filtering the filter cake to obtain a filter cake, treating the filter cake with a mixed aqueous solution of an aluminum salt and an organic alcohol, and then stirring the filter cake to obtain a mixed slurry; (2) adding a solution containing Ni, a sodium tungstate solution, a second precipitant and the mixed slurry obtained in step (1) to a reactor containing water and an oily liquid in parallel to conduct a second gelling reaction, subjecting the second precipitant to a second aging reaction after the reaction to generate a second slurry; (3) subjecting the second slurry to aging, subjecting the solid-liquid separation after the aging to the solid-liquid separation, and subjecting the solid phase to a drying and molding process to obtain a molded product; (4) The molded product is immersed in an organic acid solution containing a carboxylic acid polymer and / or an organic phosphonic acid compound, and the immersed molded product is subjected to a desalting treatment, washing, drying and roasting to obtain a core-shell structure phase hydrogenation refining catalyst; the first precipitant is an aqueous solution of an alkaline compound that does not contain nitrogen elements, and the second precipitant is an aqueous solution of sodium carbonate and / or sodium bicarbonate; the oily liquid described in step (2) is an unsaturated higher fatty acid glyceride; in the second gelling reaction of step (2), the pH value is adjusted downward from the initial value to the final pH value in batches, and the stepwise downward adjustment method is to adjust the pH value downward to the required value at that time, and keep the pH value of the reaction slurry constant until the next downward adjustment begins, and the number of downward adjustments is 2 to 10 times.

2. The method according to claim 1, characterized in that: In the solution containing Ni and Si in step (1), the weight concentration of Ni calculated as NiO is 5-120 g / L, and the weight concentration of Si calculated as SiO2 is 2-80 g / L; in the sodium molybdate solution in step (1), the weight concentration of Mo calculated as MoO3 is 5-110 g / L; and the weight concentration of the first precipitant is 5%-30%.

3. The method according to claim 1, characterized in that: The conditions of the first gelling reaction in step (1) are: reaction temperature of 30-90° C., pH value of 7.0-11.0, and gelling time of 0.2-2.5 hours.

4. The method according to claim 1, characterized in that: The first aging conditions in step (1) are as follows: the aging temperature is 60-90° C., the pH value during aging is controlled at 7.0-11.0, and the aging time is 0.3-2.5 hours.

5. The method according to claim 1, characterized in that: In step (1), the weight of the introduced Ni accounts for 30% to 80% of the total Ni weight in the hydrotreating catalyst obtained in step (4); in step (2), the weight of the introduced Ni accounts for 20% to 70% of the total Ni weight in the hydrotreating catalyst obtained in step (4).

6. The method according to claim 1, characterized in that: In step (1), the treatment process with a mixed aqueous solution of aluminum salt and organic alcohol is as follows: the mixed aqueous solution of aluminum salt and organic alcohol is slurried and mixed with the filter cake; the treatment conditions are as follows: temperature 0-30°C, time 1-16 hours; the volume ratio of the mixed aqueous solution of aluminum salt and organic alcohol to the filter cake is 1.2:1-7:1; in the mixed aqueous solution of aluminum salt and organic alcohol, the weight concentration of aluminum salt in terms of Al2O3 is 5-100 g / L; the molar ratio of the amount of organic alcohol added to Mo in the sodium molybdate solution in step (1) is 0.1-3.

0.

7. The method according to claim 1, characterized in that: The aluminum salt is one or more of aluminum chloride, aluminum nitrate, and aluminum sulfate; the organic alcohol is one or more of aliphatic alcohols with carbon numbers of C2 to C5 and dihydric alcohols with carbon numbers of C2 to C10.

8. The method according to claim 1, characterized in that: In the Ni-containing solution of step (2), the weight concentration of Ni as NiO is 5-110 g / L; in the sodium tungstate solution, the weight concentration of W as WO3 is 4-140 g / L.

9. The method according to claim 1, characterized in that: The weight concentration of the second precipitant in step (2) is 5% to 40%.

10. The method according to claim 1, characterized in that: The water in step (2) is deionized water, and the volume ratio of the added water to the volume of the first slurry obtained in step (1) is 0.1:1 to 3:

1.

11. The method according to claim 1, characterized in that: The oily liquid in step (2) is selected from one or more of peanut oil, rapeseed oil, cottonseed oil, sunflower seed oil, soybean oil, corn oil, tea oil, and olive oil; the volume ratio of the oily liquid to water is 1:60 to 1:

4.

12. The method according to claim 1, characterized in that: The conditions of the second gelling reaction in step (2) are as follows: the reaction temperature is 30-90° C., the initial pH value is controlled at 10.0-14.0, the final pH value is 7.0-8.5 at the end, and the gelling reaction time is 0.5-6.0 hours.

13. The method according to claim 1, characterized in that: The second aging conditions described in step (2) are as follows: aging temperature is 40 to 90° C., aging time is 1 to 5 hours, and pH value is 7.0 to 11.

0.

14. The method according to claim 1, characterized in that: The second aging condition in step (2) is carried out as follows: the first step is normal pressure aging: the aging temperature is 30-90°C, the aging time is 1-6 hours, and the pH value is 6.5-10.0; the second step is high pressure aging: the temperature is 100-195°C, the time is 0.1-3.5 hours, the pressure is not less than 10 MPa, and the pH value is 10.0-13.

0.

15. The method according to claim 1, characterized in that: The carboxylic acid polymer in step (4) has a molecular weight of 400 to 5000 and is selected from one or more of polyacrylic acid, polymethacrylic acid, polymaleic acid, polyaspartic acid, polyepoxysuccinic acid, acrylic acid-hydroxypropyl acrylate copolymer and maleic acid-acrylic acid copolymer; the organic phosphonic acid compound is selected from one or more of hydroxyethylidene diphosphonic acid, polyol phosphonate, 2-hydroxyphosphonoacetic acid, 1,2,4-tricarboxylic acid-2-phosphonobutane; and the organic acid is selected from carboxylic acids with a carbon number of C2 to C8.

16. The method according to claim 1, characterized in that: The organic acid in step (4) is selected from one or more of malic acid, citric acid, isocitric acid, tartaric acid, oxalic acid, succinic acid, salicylic acid, lactic acid, β-hydroxybutyric acid, maleic acid, glutaric acid, adipic acid, benzoic acid or malonic acid.

17. The method according to claim 1, characterized in that: The molar ratio of the organic phosphonic acid compound and / or carboxylic acid polymer to the organic acid in step (4) is 0.6:1 to 6:1; the molar ratio of the total molar number of the organic phosphonic acid compound and / or carboxylic acid polymer and the organic acid to the molar ratio of W in the sodium tungstate solution is 0.8 to 6.0; the liquid-to-solid volume ratio of the immersion is 1.0 to 5.0, and the immersion time is 1.0 to 12.0 hours.

18. The method according to claim 1, characterized in that: The desalination process described in step (4) is: first curing, then washing to remove the salt precipitated on the surface of the molded product, the curing conditions are a temperature of 5 to 100° C. and a time of 10 to 100 hours.

19. A bulk hydrotreating catalyst prepared by the method according to any one of claims 1 to 18, characterized in that: It comprises core-shell structured composite oxide particles, wherein the core phase is an amorphous composite oxide containing molybdenum, nickel and silicon, and the shell phase is an amorphous composite oxide containing tungsten, nickel and aluminum; the core phase is 20% to 90%, and the shell phase is 10% to 80%; the average particle size of the core-shell structured composite oxide particles is 7 to 12 nm; the particle size distribution of the catalyst particles is as follows: the number of particles with a particle size less than 7 nm accounts for 2% to 15% of the total number of particles, the number of particles with a particle size of 7 nm to 12 nm accounts for 66% to 88% of the total number of particles, and the number of particles with a particle size greater than 12 nm accounts for 3% to 21% of the total number of particles; the Na2O content in the catalyst is less than 0.12%.

20. The catalyst according to claim 19, characterized in that: The atomic molar ratio of molybdenum to nickel in the core phase is 1:28~12:1, and the content of silicon in terms of SiO2 accounts for 2%~38% of the mass of the hydrorefining catalyst; the atomic molar ratio of tungsten to nickel in the shell phase is 1:22~8:1, and the content of aluminum in terms of Al2O3 accounts for 5%~36% of the mass of the hydrorefining catalyst; the mass of NiO in the core phase accounts for 30%~80% of the total mass of NiO in the hydrorefining catalyst, and the mass of NiO in the shell phase accounts for 20%~70% of the total mass of NiO in the hydrorefining catalyst.

21. The catalyst according to claim 19, characterized in that: The pore size distribution of the catalyst is as follows: the pore volume occupied by pores with a diameter of less than 4 nm accounts for 1%~10% of the total pore volume, the pore volume occupied by pores with a diameter of 4~10 nm accounts for 12%~40% of the total pore volume, the pore volume occupied by pores with a diameter of 10~15 nm accounts for 22%~56% of the total pore volume, and the pore volume occupied by pores with a diameter of more than 15 nm accounts for 18%~45% of the total pore volume.

22. Use of a bulk hydrotreating catalyst prepared by the method according to any one of claims 1 to 18 in the hydrotreating reaction of inferior distillate oil.

Citation Information

Patent Citations

  • Super-deep fraction oil hydrodesulphurization catalyst and preparation method thereof

    CN102049295A

  • Method for preparing hydrogenation catalyst composition

    CN102451706A

  • A hydrofining catalyst and its preparation method

    CN106179474B

  • Preparation method of bulk-phase hydrofining catalyst

    CN106513006A

  • Method for preparing hydrofining catalyst

    CN110038581A

Cited By

  • A core-shell structure catalyst for hydrogenation of waste plastic cracking oil, a preparation method and application thereof

    CN122682627A

  • A core-shell structure catalyst for hydrogenation of waste plastic cracking oil, a preparation method and application thereof

    CN122682627B